Floristic study of a maërl and gravel subtidal bed in the ‘Ría de Arousa´ (Galicia, Spain) - Veiga, Alfredo J.; Bárbara, Ignacio; Cremades, Javier (Botanica Complutensis, 2005)
Bárbara, I.; Cremades, J. & Veiga, A. J. 2004. Floristic study of a maërl and gravel subtidal bed in the `Ría de Arousa' (Galicia, Spain). Bot. Complut. 28: 27-37. A catalogue of 68 species of seaweeds associated with a subtidal maërl and gravel bed in the «Arousa Ría» (Galicia, Spain) is presented. Colacodictyon reticulatum and Gelidiella calcicola are new for the Iberian Peninsula. Other interesting species are Stylonema cornu-cervi, Cruoria rosea-stage, C. cruoriaeformis, Trailliella intricata-stage, Hymenoclonium serpens-stage, Dasya punicea, Heterosiphonia japonica, Symphyocarpus strangulans and Desmarestia dudresnayi. In Dasya punicea spermatangial stichidia are described for the first time. Seasonal floristic variations in the subtidal maërl and gravel bed are described. Species adapted to this biogenic, unstable substratum with crustose or prostrate forms, like Cruoria cruoriaeformis, C. rosea-stage, Peyssonnelia dubyi, Symphyocarpus strangulans, Aglaozonia parvula-stage and Gelidiella calcicola, are abundant. The vegetation exhibits prominent seasonal variations: in winter the vegetation remains dormant (as crustose growth forms) but in summer produces erect foliose thalli. The alternation of these biological stages has heteromorphic cycles in which the crustose stages provide constant populations during the unfavourable season and the later development of the erect phase of species.
Keywords: seaweeds; maërl; Iberian Peninsula; Spain; Galicia; subtidal; Colacodictyon reticulatum; Gelidiella calcicola